Complimentary Split Ring Resonators Design On Patch Mikrostrip Antenna For Reducing Ads-B Antenna Dimension - Habib Muharry Yusdartono; Andik Bintoro; Badriana Badriana; Ummu Handasah (Universitas Medan Area, 2022)
Microstrip Patch Antenna works for Automatic Dependent Surveillance – Broadcast (ADS-B) and antenna frequency resonances at 1.09 GHz. Microstrip Patch Antenna dimension has big shape for antenna micostrip resonancing frequency at 1.09 GHz. In order to Solve this problem, metamaterial is chosen and Complimentary Split Ring Resonators (CSRRs) is the one of metamaterial technique. Complimentary Split Ring Resonators CSRRs is derived from a Split Ring Resonator (SRR) compliment. Early dimension of Microstrip antenna substrate and patch are calculated by Equation that dimension of substrate is 137x130 mm and dimension of patch is 85x65. Dimension of SRR that compliment forms to CSRRs is 9x6 mm for SRR inner ring and 13x10 mm for outer ring. Microstrip antenna VSWR is 1.134 and VSWR increases to 22,73 when CSRR is etched on antenna patch. In order to decrease antenna VSWR, optimation is applied by substrate and patch dimension iteration. Substrate and patch dimension Iteration is enlarge and reduce antenna substrate and patch width and length. Optimation result is VSWR that VSWR comes to 1,559 and substrate and patch dimension is reduced to 27,9% and 14,1%.